A Multi-Level Approach to Investigating Neighborhood Effects on Physical Aggression among Urban Chicago Youth - Jennings, Wesley G. (American journal of criminal justice, 2011)
The current study evaluates neighborhood effects, individual-level effects, and demographic characteristics that influence physically aggressive behavior among urban youth. Using data derived from 5,812 adolescents from Project Northland Chicago (PNC) and Heirarchical Linear Modeling (HLM) techniques, the results suggested that neighborhood problems significantly predicted physical aggression, before and after adjustment for individual-level risk factors (alcohol use, peer alcohol use, lack of adult supervision, and depression) and demographics. After accounting for baseline physical aggression, however, neighborhood problems were no longer a significant predictor of physical aggression. Implications for intervention at both the neighborhood and individual-level and study limitations are also discussed.